2014
DOI: 10.1136/annrheumdis-2014-206028
|View full text |Cite
|
Sign up to set email alerts
|

The JAK inhibitor tofacitinib suppresses synovial JAK1-STAT signalling in rheumatoid arthritis

Abstract: ObjectiveTofacitinib is an oral Janus kinase (JAK) inhibitor for the treatment of rheumatoid arthritis (RA). The pathways affected by tofacitinib and the effects on gene expression in situ are unknown. Therefore, tofacitinib effects on synovial pathobiology were investigated.MethodsA randomised, double-blind, phase II serial synovial biopsy study (A3921073; NCT00976599) in patients with RA with an inadequate methotrexate response. Patients on background methotrexate received tofacitinib 10 mg twice daily or pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
170
0
10

Year Published

2015
2015
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(191 citation statements)
references
References 28 publications
7
170
0
10
Order By: Relevance
“…The results indicate that or the knee joint core needle biopsy is the most suitable procedure in this setting notably due to a low invasiveness, high superficial synovial layer tissue yield and good visualization. The results presented here are in line with the recommendations of the EULAR synovitis study group favoring needle-based approach for synovial biopsy over arthroscopy despite arthroscopy-guided techniques still are applied in current studies [10]. The integrated needle system demonstrated here seemed also suitable for hrMSUS-guided biopsy.…”
Section: Discussionsupporting
confidence: 77%
“…The results indicate that or the knee joint core needle biopsy is the most suitable procedure in this setting notably due to a low invasiveness, high superficial synovial layer tissue yield and good visualization. The results presented here are in line with the recommendations of the EULAR synovitis study group favoring needle-based approach for synovial biopsy over arthroscopy despite arthroscopy-guided techniques still are applied in current studies [10]. The integrated needle system demonstrated here seemed also suitable for hrMSUS-guided biopsy.…”
Section: Discussionsupporting
confidence: 77%
“…Previous suggestions included a suppression of pathogenic Th1/Th17 differentiation (7,25) or a local effect on IFN and IL-6 signaling in RA joints (26). Our results flag innate cell populations as alternative or additional contributors.…”
Section: Discussionmentioning
confidence: 52%
“…Boyle at al. showed that changes in synovial phosphorylation of STAT1 and STAT3 strongly correlated with four-month clinical responses in RA patients treated with 10 mg of tofacitinib twice a day [26].…”
Section: Discussionmentioning
confidence: 99%